Dasar Kewenangan Notaris dalam Membuat Covernote - Dino Rafly Priatna (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This research is about the Authority of Notaries to Make Covernotes. Regarding making covernotes by Notaries, until now there is no legal umbrella, but in practice Notaries make covernotes in the credit agreement process. This type of research is empirical juridical research and uses a statutory legal approach. The research data used is secondary data and primary data. Secondary data is data obtained from interviews with Notaries in the City of Yogyakarta and the Chair of the Regional Supervisory Council of the Special Region of Yogyakarta Province. Secondary data comes from legislation and other legal materials. Research data was analyzed using a quantitative approach. The results of this research explain: Covernotes are made based on custom and based on material law, namely the law of engagement. If there is a formal legal source in the form of custom, it is acceptable, does not conflict with the law and is carried out repeatedly, which causes the action to be considered the truth and does not conflict with applicable law. .Even though the position of the covernote is still considered not to meet legal certainty. Covernotes have also been explicitly discussed by the Management of the Indonesian Notary Association that the UUJN does not regulate the making of covernotes by Notaries regarding activities or implementation of Notarization.